Hábitat micro temporal (2020)
The tenancies or Inquilinatos are a historical, collective, temporary and informal form of living in Bogotá. Although in the past itþs population was heterogeneous, today it is home to the most vulnerable population. Most of the times, this type of living is the only available housing option for informal workers, Venezuelan immigrants and people displaced by violence. This is due to the payment method of tenancy, its central location and itþs simple access. However, the problem lies within the living conditions of these spaces, which are generally precarious. They are overcrowded, presenting habitability and sanitation problems. Understanding the social context and how the Inquilinatos currently work, this project proposes a model of collective living that establishes the individual as a priority. Based on the micro-housing typology, the flexible units are proposed to respond not only to the basic needs, but also to be grouped and ungrouped temporarily. In this way, the living model responds to different kinds of families.